PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI SAINS SISWA KELAS XII PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN - Khairul Mahdi; Adnan; Andi Rahmat Saleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of the 21st century is increasingly complex both in the fields of knowledge, technology and information globally, basically aimed at improving the quality of life of society. This type of research is a quasi-experimental (Quasi Experiment). This study aims to determine how the scientific literacy skills of high school students in classes taught using problem-based learning models and classes taught with direct instruction models, as well as to determine the effect of problem-based learning models on the scientific literacy skills of high school students. The design of this study is a pretest - posttest control group design. The population of this study were students of class XII MIPA SMAN 2 Makassar. The research sample was Class XII MIPA 2 and XII MIPA 4. The research instrument in this study was a scientific literacy ability test in the form of multiple-choice questions totaling 14 numbers. The data were analyzed using descriptive statistics and inferential statistics, including normality tests, homogeneity tests, and hypothesis testing using analysis of covariance. The results of the scientific literacy analysis showed that students who implemented the problem-based learning model performed better than those who implemented the direct instruction model. This was evidenced by the average pretest scientific literacy score of 65.61 for the experimental class, which falls into the moderate category, and the control class, which falls into the low category (61.96). The posttest score of 87.23 for the experimental class, which falls into the very high category, and 71.48 for the control class, which falls into the moderate category. This suggests that problem-based learning has an impact on students' scientific literacy skills.